Educational Empowerment in Managing Means and Infrastructure on Faculty of Teacher Training and Education (FKIP) at Tanjungpura University - M. Chiar (STKIP Singkawang, 2018)
Empowerment is the giving of strength to individuals or groups to be more empowered than before and has a responsibility in exercising the authority entrusted to them. Therefore, empowerment is essential for an institution as a form of enormous internal power contributing to the institution. With the empowerment, institutions are increasingly responsive to change, renewal science, and technology, especially in the field of education which continues to grow following the demands of the times. This research focuses on empowering education personnel in managing facilities and infrastructure at the Teacher Training and Education Faculty. The focus of this study is